2021
DOI: 10.1038/s41598-021-03656-3
|View full text |Cite
|
Sign up to set email alerts
|

Zooplankton diversity monitoring strategy for the urban coastal region using metabarcoding analysis

Abstract: Marine ecosystems in urban coastal areas are exposed to many risks due to human activity. Thus, long-term and continuous monitoring of zooplankton diversity is necessary. High-throughput DNA metabarcoding has gained recognition as an efficient and highly sensitive approach to accurately describing the species diversity of marine zooplankton assemblages. In this study, we collected 30 zooplankton samples at about 2-week intervals for 1 year. Zooplankton diversity showing a typical four season pattern. Of the “t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 45 publications
(49 reference statements)
2
13
0
Order By: Relevance
“…Our research aims to contribute genetic identification methodology, ground-truthed with zooplankton morphological identifications, towards understanding and monitoring the dynamic responses of zooplankton and ichthyoplankton species and their communities in future studies. Here we employ a high-throughput sequence (HTS) metabarcoding assay approach, which prior studies have indicated can capture a broad diversity of taxa that are often difficult to identify using microscopy and/or other morphological techniques; these include many larval bivalves, gastropods, polychaetes, copepods, and fishes [28][29][30][31][32]. Metabarcoding can also detect species that are low in abundance and/or cryptic [3,9,[29][30][31][32][33][34][35][36].…”
Section: Metabarcoding Markers Evaluated For the Zooplankton And Icht...mentioning
confidence: 99%
See 4 more Smart Citations
“…Our research aims to contribute genetic identification methodology, ground-truthed with zooplankton morphological identifications, towards understanding and monitoring the dynamic responses of zooplankton and ichthyoplankton species and their communities in future studies. Here we employ a high-throughput sequence (HTS) metabarcoding assay approach, which prior studies have indicated can capture a broad diversity of taxa that are often difficult to identify using microscopy and/or other morphological techniques; these include many larval bivalves, gastropods, polychaetes, copepods, and fishes [28][29][30][31][32]. Metabarcoding can also detect species that are low in abundance and/or cryptic [3,9,[29][30][31][32][33][34][35][36].…”
Section: Metabarcoding Markers Evaluated For the Zooplankton And Icht...mentioning
confidence: 99%
“…Here we employ a high-throughput sequence (HTS) metabarcoding assay approach, which prior studies have indicated can capture a broad diversity of taxa that are often difficult to identify using microscopy and/or other morphological techniques; these include many larval bivalves, gastropods, polychaetes, copepods, and fishes [28][29][30][31][32]. Metabarcoding can also detect species that are low in abundance and/or cryptic [3,9,[29][30][31][32][33][34][35][36].…”
Section: Metabarcoding Markers Evaluated For the Zooplankton And Icht...mentioning
confidence: 99%
See 3 more Smart Citations